2021
DOI: 10.1088/1755-1315/800/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of heritability in three months old sengon (Falcataria moluccana) seedlings at a progeny testing in Kediri, East Jawa, Indonesia

Abstract: Heritability values were estimated for three months old seedlings height and diameter of Sengon (Falcataria moluccana) grown in a progeny testing in Kediri, East Jawa, Indonesia. Totally 10.000 seedlings from 100 families were planted, consisting of 50 families from resistant mother trees to boktor pest (Xystrocera festiva) and gall rust disease (Uromycladium falcatariae) and other 50 families from susceptible ones. The progeny testing applied split-plot block design with four blocks, 100 families as sub-plot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Moreover, the aluminum (Al) content in the soil affected the growth of seedlings (Salim et al 2021). Previous research suggested that sengon seedling production's primary issue was related to failure (Hakim et al 2009;Siregar et al 2021). Therefore, research in risk analysis is imperative to design measures that minimize failures and improve seedling production.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the aluminum (Al) content in the soil affected the growth of seedlings (Salim et al 2021). Previous research suggested that sengon seedling production's primary issue was related to failure (Hakim et al 2009;Siregar et al 2021). Therefore, research in risk analysis is imperative to design measures that minimize failures and improve seedling production.…”
Section: Introductionmentioning
confidence: 99%